1959
DOI: 10.1042/bj0730305
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial degradation of the nitrobenzoic acids. 2. Reduction of the nitro group

Abstract: has been observed. The fundamental importance of this reaction is emphasized by the work of de la Haba (1950) and McElroy & Spencer (1956), from which the suggestion arose that nitro compounds are probably intermediates in the reduction of nitrates by green plants and microorganisms , and the finding that moulds and higher plants, in the absence of added nitro compounds or their presumed precursors, elaborate enzymes capable of metabolizing nitro compounds (Bush, Touster & Brockman, 1951; Shimoda, 1951; Raistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

1969
1969
2004
2004

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…1), yet further analysis of the genes has shown that pnbA, encoding the primary reduction of 4NBen, is not located on either plasmid. However, there is substantial evidence that nitro groups can be reduced nonspecifically by a variety of dehydrogenase/reductase reactions (10,23,26,32), and in many situations where there are no specific degraders present, reduced derivatives often accumulate; this is particularly true in anaerobic environments where the nitro groups can be reduced completely to the corresponding amino groups (11). It is possible that nitroreductases in E. coli such as NfsA and NfsB (8,25,41,44) can effect the partial reduction of 4NBen, thus complementing pnbA and allowing PnbB on plasmids pTW3.11 and pTW3.12 to produce sufficient quantities of PCA to be visualized on the p-toluidine plates.…”
Section: Discussionmentioning
confidence: 99%
“…1), yet further analysis of the genes has shown that pnbA, encoding the primary reduction of 4NBen, is not located on either plasmid. However, there is substantial evidence that nitro groups can be reduced nonspecifically by a variety of dehydrogenase/reductase reactions (10,23,26,32), and in many situations where there are no specific degraders present, reduced derivatives often accumulate; this is particularly true in anaerobic environments where the nitro groups can be reduced completely to the corresponding amino groups (11). It is possible that nitroreductases in E. coli such as NfsA and NfsB (8,25,41,44) can effect the partial reduction of 4NBen, thus complementing pnbA and allowing PnbB on plasmids pTW3.11 and pTW3.12 to produce sufficient quantities of PCA to be visualized on the p-toluidine plates.…”
Section: Discussionmentioning
confidence: 99%
“…The nitro anion radical reacts with oxygen to form superoxide and regenerate the parent nitro compound (6). Oxygen-insensitive (type I) enzymes reduce the nitro group in a series of two-electron transfers to produce the corresponding nitroso, hydroxylamino, and amino derivatives (9,40). Even though the nitroso intermediate is so reactive that it is difficult to isolate from biochemical reactions, its role can be inferred from studies of nitro compounds reduced in controlled chemical reactions (11).…”
mentioning
confidence: 99%
“…Sub strates for these enzymes range from the nitrofuran antibiot ics to nitroarenes such as 1-nitropyrene, and also include nitroaromatic explosives such as 2,4,6-trinitrotoluene (TNT). The compounds most commonly observed during nitroreduction of nitroaromatics are aromatic hydroxylamines (Cartwright et al 1959;Kaplan 1990;McCalla et al 1970;McCormick et al 1976;Mori et al 1984;Schackmann and Müller 1991;Schenzle et al 1999). However, evidence does exist for the formation of a nitroso functional group during biological reduction of some nitroaromatics (Liu et al 1984).…”
mentioning
confidence: 99%